THE ROLE OF DOMESTIC ENVIRONMENT IN THE INCIDENCE OF FALLS IN ELDERLY (Fiep Bulletin - online, 2012)
The Ministry of Health, Brazil experienced a significant increase in the number of elderly. Among the factors that contribute to worsening health conditions an life of the elderly population there are the falls, which are the main cause of accidents in people over 60 years in his home. Fall is a factor which has the unintended result of the change in position of the individual to a lower level compared to its initial position, with a growing problem in an aging population every day. The extrinsic causes are a major cause of falls in the home, causing physical and psychological consequences for the elderly. We conducted this study aiming to analyze the influence of home environment and extrinsic factors in the causes of falls. We used a questionnaire with closed questions, applied for 5 health workers in Lages / SC, interviewing 41 individuals, 26 women and 15 men in their homes. And applied the scale adapted Fall Risk Score, which aims to assess the risk of falls, using the numerical values ??obtained, ranking high, medium and low risk. The results show that 71% of respondents have had episode of fall, and 49% suffered some type of fracture, 27% were hospitalized and 17% had bruises. The highest incidence of falls occurred in the bathroom (37%) and fourth (25%). It was evident that the risk for falls increases with the number of extrinsic factors, whereas 84% ??of respondents have a high risk of falls. Therefore, it is essential to monitor the elderly physiotherapy, seeking environmental adaptation, physical activity, improving balance and mobility, ensuring greater autonomy and independence to these elderly, and thus preventing falls in the home environment.
Keywords: elderly; home environment; falls.